2017
DOI: 10.1111/apa.14000
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17A gene polymorphism rs2275913 is associated with osteitis after the Bacillus Calmette‐Guérin vaccination

Abstract: IL17A rs2275913 gene polymorphism was associated with a risk of BCG osteitis after vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In our previous study on IL17A polymorphisms in this same cohort, IL17A rs2275913 variant genotype 13 and IL17A haplotypes including the rs2275913 variant allele, 14 when compared with population‐based controls, were associated with increased BCG osteitis risk after newborn vaccination. It is important to note that IL‐17F mainly acts as a heterodimer with IL‐17A, 24 and for significant consequences, some deficiency needs to be in both cytokines.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In our previous study on IL17A polymorphisms in this same cohort, IL17A rs2275913 variant genotype 13 and IL17A haplotypes including the rs2275913 variant allele, 14 when compared with population‐based controls, were associated with increased BCG osteitis risk after newborn vaccination. It is important to note that IL‐17F mainly acts as a heterodimer with IL‐17A, 24 and for significant consequences, some deficiency needs to be in both cytokines.…”
Section: Discussionmentioning
confidence: 77%
“…Originally, 222 children with BCG osteitis after newborn vaccination in 1960‐1989 were included in our cohort. In 2007‐2008, 132 former BCG osteitis patients gave blood samples for further studies, and as published previously, the variant genotype of IL17A rs2275913 13 and the haplotype including the variant allele of IL17A rs2275913 14 increased the BCG osteitis risk.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several meta-analysis demonbstrated the relationship between gene polymorphisms of IL-17A (rs2275913) and IL-17F (rs763780) and the pathogenesis of in ammatory diseases, including periodontitis, SLE, golomerulonephritis, rheumatoid arthritis (RA), and in ammatory bowel disease [12]. Research also reported polymorphism of IL17A (rs2275913) is associated with osteitis after the Bacillus Calmette-Guérin vaccination [18,19], and a variant of IL17F (rs763780) may participate in the development of immune thrombocytopenia [20] and necrotizing enterocolitis [21]. All these researches indicate that IL17 polymorphisms are possibly associated with immune mediated diseases widely.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rs2275917 SNP may reflect the autoimmune‐related function of IL‐17A. With regard to the function of IL‐17A in preventing infection, the AA genotype of the rs2275913 SNP was shown to be associated with protection against tuberculosis but also higher disease severity, hepatitis B virus (HBV) resistance, and Bacillus Calmette–Guérin (BCG) osteitis after vaccination . These findings indicate that the AA genotype of the rs2275913 SNP has advantages for preventing infections, whereas this genotype overall leads to more severe inflammation.…”
Section: Introductionmentioning
confidence: 99%